ALA, Fatty Fish or Marine n-3 Fatty Acids for Preventing DM?: A Systematic Review and Meta-Analysis - Muley, Arti; Muley, Prasad; Shah, Monali (Current Diabetes Reviews, 2014)
Diabetes mellitus (T2DM) has become a global problem. Role of n-3 FA in its prevention is still not completely understood. We carried out this systematic review and meta-analysis to assess the relation of dietary intake of fish and n-3PUFA with risk of diabetes. We searched PUBMED, EMBASE and GOOGLE with cross references to identify relevant articles. Since no RCTs were available, we searched for prospective cohort studies. Sixteen studies with 6,79,763 participants which assessed the association of dietary intake of fish and n-3 PUFA (marine or alpha-linolenic acid) with incidence of T2DM in > 18 years population and provided relative risk (RR) or hazard ratio (HR) with the corresponding 95% confidence interval (CI) of T2DM for each category of fish or n-3 PUFA intake were included. Three independent reviewers reviewed all eligible studies and abstracted the relevant information from individual studies. Meta-analysis confirmed the previous finding that marine n-3 FA increased risk of T2DM in Americans but reduced the same in Asians. We observed that two and seven times increased intake of ALA and fatty fish respectively reduced the risk of T2DM significantly and ALA did not increase the risk in Americans. We concluded that ALA may have some role in preventing T2DM, but is not studied widely. Hence, it should be studied in greater details (with higher degrees of intake; more than two times) to aid in developing effective preventive strategies against diabetes.
Keywords: marine omega3 fatty acids